The Study of Serum Levels of AST, ALT, GGT, Serum Bilirubin in Relation to OGTT in Patients with NAFLD - Srikanth, Mannava Prasanthi (Asian Journal of Medical Research, 2017)
Background: Nonalcoholic fatty liver disease [NAFLD] is a very common disorder and refers to a group of condition where there is accumulation of the excess fat in the liver who drink no alcohol. The most common form of NAFLD is not a serious condition called Fatty liver. In fatty liver, fat accumulates in the liver cells. The presence of fat in the liver; it probably does not damage the liver. A small group of people with NAFLD can progress to a condition called Nonalcoholic steatohepatitis [NASH]. Thus World Gastroenterology Organisation guidelines proposes Aspartate Transaminase [AST], Alanine Transaminase [ALT], Gamma Glutamyl Transferase [GGT] and other markers of liver injury may be used to diagnose NAFLD. Now a days NAFLD is closely related to Obesity, insulin resistance, metabolic syndrome, IGT, Pre diabetes and diabetes. Methodology: This is a prospective study was conducted in the Department of Biochemistry at Tertiary Care Teaching Hospital over a period of 1 year. Study subjects were selected from department of Radiology and Medicine both outpatient and inpatient who are found to have fatty liver by ultrasound and the biochemical analysis was done in the department of Biochemistry. The study includes 30 people without NAFLD 30 patients with NAFLD. Age is more than 40 years and both males and females are taken. Results: In the present study the mean value of GGT in group1 is 23.50+6.83 and in group 2 is 55.77+11.44. p value is <0.001 which is statistically significant. In the present study the mean value of TSB in group1 is 0.75+0.13 and in group2 is 1.32+0.20. there is significant increase in the mean value in Group2 and the p value is <0.001 which is statistically significant. In the present study the mean value of FPG in group1 is 83.87+8.58 and in group2 is 117.83+8.51. There is increase in the mean value in Group2 when compared to Group1 and the p value is <0.001 which is statistically significant. In the present study the mean value of 1-Hour post glucose load in group1 is 138.13+7.61 and in group2 is 191.90+14.53. p value is <0.001 which is statistically significant. Conclusion: The serum levels of liver enzymes with glucose values of OGTT are compared; there is significant rise in the glucose values and the liver enzyme values in NAFLD cases. Hence NAFLD patients may benefit from early screening for Diabetes mellitus. NAFLD is the most common chronic liver condition in adults and is present in the majority of obese people. It may lead to serious medical complications ranging from cryptogenic cirrhosis to hepatocellular carcinoma as well as DM and CVD.